A Comparative Study in the (myth of Pygmalion) between Bernard Shaw and Sadik Hidayat: University of Ferdowsi - Iran (Journal of the College of Education for Women, 2019)
In our time, not too long ago, the universities of the world have been fast to take care of the study of an innovative type of technical and human studies, called the science of "comparative literature". Comparative research studies have grown and flourished rapidly in response to the demands of both mental and artistic life. This shows the increasing awareness at both the modern national and the international levels in order to develop through connecting with the international intellectual, nental and artistic currents to nurture ethics and originality. Comparative studies show that the beginning of the comparative literature goes back to the time when the Latin literature was connected to the Greek literature and the comparative literature was shaped in the era of European Renaissance. Today, it is one of the most authentic sciences in universities, with complex branches, due to its being an inevitable result of increasing human awareness and the result of the great demand by the conscious public to benefit from the many human and cognitive aspects provided by the comparative literature through its connection